Effect of Pumice Stone and Sugar Molasses on the Behavior of Reinforced Concrete One-Way Ribbed Slabs - Mohammed, Tamara Amer; Kadhim, Hayder Mohammed (Civil Engineering Journal, 2022)
The world is currently heading towards sustainability by reducing the amount of concrete, thus reducing the total unit weight. Moreover, design construction requires materials with a higher strength-to-weight ratio. Ribbed slabs and lightweight concrete (LWC) are considered two leading sustainability facilities. This research developed an experimental study to evaluate the effects of concrete type, steel reinforcement ratio, the geometry of ribs, voiding ratio, and slab type on the structural behavior of one-way ribbed slabs. Eight of the one-way slabs were constructed using pumice stone and by-product material sugar molasses (SM), and one slab was constructed using gravel and SM. These slabs were tested under a static two-point load and simply supported until failure. The results showed that using SM with pumice stone instead of gravel led to high strength-lightweight concrete (HSLWC), with a cylinder compressive strength of 42.2 MPa and a density of 1943 kg/m3, which meets the requirements of HSLWC codes. Using HSLWC instead of high-strength normal-weight concrete (HSNWC) decreased the thermal conductivity by 43.55% and the unit weight by 19.31%. Moreover, the ultimate strength of the HSLWC one-way ribbed slab decreased by 17.70%. Overcoming this strength reduction necessitated increasing the steel reinforcement ratio of the ribs from 0.28 to 0.44% in the HSLWC ribbed slab. Changing the number of ribs at the same amount of HSLWC showed a minor effect on the strength capacity of slabs but showed an economic benefit. However, increasing the rib width to reduce the voiding ratio from 44 to 40% resulted in a greater improvement in structural efficiency (SE) of one-way ribbed slab than reducing it from 44 to 33%. Consequently, the optimum rib width was 120 mm. Moreover, using a ribbed slab instead of a solid slab of HSLWC at the same amount of concrete increased the ultimate strength by 130.37%, decreased deflection by 3.99%, and improved SE by 126.46%. Furthermore, experimental results of ultimate load were compared with the ACI 318-19 code design equation.Â Doi: 10.28991/CEJ-2022-08-02-011 Full Text: PDF